High Availability for Critical Services Using Open Software and Virtualization - Caciato, Luciano Eduardo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
This article presents a proposal to solve the problem of unavailability of services in the level of the operating systems hosted on virtual machines. The proposal is based on the use of open software in order to attend a demand reported in the literature in which we can find some restricted solutions limited to the level of virtualization.